Etos Dan Visi Gerakan Muhammadiyah - A. Jusmawati .; Strisna Syafar; M. Amin (CV. ITTC INDONESIA, 2026)
Muhammadiyah is an Islamic movement founded by Ahmad Dahlan in 1912 with the aim of promoting reform (tajdid) in Muslim society. The ethos of Muhammadiyah is grounded in the purification of Islamic teachings based on the Qur’an and Sunnah, a spirit of reform, rationality, and a strong orientation toward concrete social action. The movement emphasizes education, social services, healthcare, and community empowerment as manifestations of enlightened and progressive da‘wah. Muhammadiyah’s vision is the realization of a truly Islamic society—one that upholds sound faith, noble character, justice, prosperity, and a high level of civilization. Through its reformist ethos and transformative social vision, Muhammadiyah plays an active role in advancing religious, national, and humanitarian life based on progressive and inclusive Islamic values.